Organizational Behavior And Culture In Education - Septianto Saleh, Yusuf Yusian; Arifiani, Bilqis Fathimatus (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2024)
Organizational behavior is a field of study that examines habits, behavior, and the impact of individual involvement with organizations that influence processes within organizations such as in organizations or educational institutions. Organizational culture in education is something that is carried out continuously, making it a characteristic of an educational institution. Organizational behavior and culture in education is a unit that forms a structured system and shapes individual behavior patterns in organizations or educational institutions. The objectives of this research are 1) the concept of organizational behavior in education; 2) the concept of organizational culture in education; 3) behavioral and cultural characteristics of educational organizations. The research method used is a library study that focuses on literature, books, notes and published scientific information. The results of this research are 1) organizational behavior is a study that discusses individuals to obtain information in making decisions to make rules that can be used according to the conditions and situations of the educational environment; 2) organizational culture is the basic assumptions developed within an organization, to serve as a guide for the attitudes and behavior of all its members; 3) the characteristics contained in organizational behavior and culture in education are habits that are carried out repeatedly or continuously in learning to produce a certain behavior and culture that has characteristics that are different from other aspects.